Depositional age models in lacustrine systems from zircon and carbonate U‐Pb geochronology. Issue 6 (30th May 2022) - Montano, Damaris; Gasparrini, Marta; Rohais, Sébastien; Albert, Richard; Gerdes, Axel
Abstract: The Yacoraite Formation (Salta rift, Argentina) consists of Maastrichtian–Danian lacustrine carbonate and siliciclastic deposits with interbedded volcanic ash layers, organized in four third‐order stratigraphic sequences. It offers the exceptional opportunity to jointly apply in situ zircon and carbonate U‐Pb geochronology that resulted in two distinct depositional age depth models. Ages of the youngest zircon population from ash layers were linearly interpolated to derive a zircon depositional age depth model. A carbonate depositional age depth model was instead obtained from dated carbonate phases including microbialites, ooids, oncoids of calcitic and dolomitic mineralogy as well as early lacustrine calcite cements. Mean ages were defined from different carbonate phases belonging to the same layer and then linearly interpolated. Sedimentation rates were calculated from both depth models between pairs of dated samples and used to estimate the age of sequence boundaries, as well as the duration of the four stratigraphic sequences. The zircon and carbonate depositional age depth models agree with biostratigraphic constraints and exhibit excellent consistency. The onset and end of sedimentation were estimated at 68.2 ± 0.9 Ma and 62.3 ± 0.6 Ma (duration ca 5.7 Ma) via zircon geochronology and at 67.9 ± 1.7 Ma and 61.9 ± 1.3 Ma (duration ca 6.0 Ma) via carbonate geochronology. Results from this study show that with suitable samples and a newly implemented working strategy, in situ U‐Pb dating of depositional and early diagenetic carbonates represent a valuable chronostratigraphic tool for estimating sedimentation rate and duration in poorly time‐framed depositional systems.